Training on Governance of Rugemuk Village Tourism Destinations and Making Ecoprint Souvenirs - Arwina, Arwina Sufika; Ridwanti, Ridwanti Batubara; Solahuddin , Solahuddin Nasution (Talenta Publisher, 2020)
Rugemuk Village in Pantai Labu Subdistrict, Deli Serdang Regency, North Sumatra Province has a beach area called Alam Serdang Beach with the presence of a mangrove forest area that has been used to produce processed mangrove products and tourist destinations. It's just that since 2006 there have been activities of dredging beach sand for the sake of building public facilities in North Sumatra Province so that Alam Serdang Beach has experienced an abrasion. The purpose of community service activities is to train the Serdang Nature Group as a partner on the management of Serdang Alam Beach tourism destinations and making eco print souvenirs by utilizing leaves from trees that grow in the Serdang Alam Beach area, as well as providing mandatory facilities in tourist destination areas. Methods of activity include providing questionnaires and training materials, discussion and design of tourism destination management, training on making souvenirs for printing, making toilet facilities, andsignposts. The results of this activity are an increase in public knowledge of tourism destination management, availability of management planning for the Alam Serdang Beach area, availability of toilet facilities on the beach, availability of signposts to the beach, improvement of community skills for making eco print souvenirs, and availability of production tools. for the making of eco print souvenirs so that it is hoped that in the future it can be the readiness of Rugemuk Village in an effort towards the level of a tourist village